Performance Assessment of Moratuwa- Ratmalana Biological Nutrient Removal Industrial Wastewater Treatment Plant - Danushika, U.A.A.G.; Bandara, N.J.G.J.; Rupasinghe, S.K.L.S. (Proceedings of the International Forestry and Environment Symposium 2016, Department of Forestry and Environmental Science, University of Sri Jayewardenepura, Sri Lanka., 2016)
Attached

This study evaluates the performance o f Moratuwa-Ratmalana Biological Nutrient Removal (BNR) plant during the dry period o f 2016. This treatment plant is 1st ever reverse A2/0 (anoxic/ anaerobic/ aerobic) treatment plant in Sri Lanka which was established by the National Water and Drainage Board (NW DB) in 2013. This study was confined to the dry period. This study was carried out to achieve two objectives. First objective is to monitor and evaluate the overall efficiency o f the treatment plant in terms o f removing pollutants from the influent. Second objective is to analyze nitrogen and phosphorous removing ability in each compartment. Samples were collected weekly for a stretch o f 15 weeks from February to May. The sampling method utilized in this study was ‘grab sampling’ and ‘composite sampling’. First samples from each three layers o f each o f the three compartments were collected through grab sampling and then composite samples for each layer was prepared by using the grab samples. Composite samples were used for final testing. In addition samples were also collected for influent and effluent from the composite sampler which is located in the treatment plant. The analysis was carried out to test for physical (pH, Temperature) and chemical (BOD, COD, TSS, TP, TN) parameters o f each collected sample. The performance evaluation has indicated that 88.52% COD removal, 97.05% TSS removal, 94.12% BOD removal, 84.23% o f TP removal and 81.65% o f TN removal efficiencies have been achieved. A lso the analytical measurements obtained o f the treated effluent are compatible with the discharge water quality standards issued by CEA, Sri Lanka. In addition it was shown that each compartment o f the treatment plant meets the design expectations regarding Nitrogen and Phosphorous removing abilities.
Keywords: Wastewater Treatment; Plant performance; Reverse A2/0